What Physical Education Trainees Think about Teaching Profession and Mentoring during a TVET Practical Traineeship? - Melki, Hassan; Bouzid, Mohamed Sami (Journal of Technical Education and Training, 2021)
The attitude of futures teachers of physical education and mentorship, are two mainvariables that may affect the number of student teachers being part of the profession, particularly in physical education universities that offer technical and vocational education and training (TVET).Therefore, the purpose of this study is to investigate attitudes of pre-service teachers toward the physical education teaching profession. In addition, this research attempts to understand whether the relationship between mentors and students affects the transfer of learning from the university during a practical teaching internship.This is a quantitative study using a questionnaire to examine attitudes towards the teaching profession and understand the views on mentoring of 169 physical education students in Tunisia to illustrate the importance of professional mentoring work.A descriptive statistics including means and standard deviations were used to describe each item and the mean of all items for each scale. In this context, SPSS (Statistical Package for Social Sciences) 16.0 software was applied.It was revealed that student teachers' answers were significantly higher while taking into consideration both of university teaching methods and of advice of university supervisor. These findings pave the way for integral implications: a greater transition from university learning to practice, producing future teachers who are ready to integrate and implementing university practices in a new context.